The application of a problem-based learning model to increase student learning activeness on ecosystem material in class x agribusiness of food crops and horticulture at state vocational high school 1 hilimegai in the 2022/2023 academic year - Marsia Adimani Ndruru (Journal of Education Innovation and Curriculum Development, 2023)
The character of students in Class X Agribusiness of Food Crops and Horticulture of State Vocational High School 1 Hilimegai for ecosystem material was previously less active in learning Biology, this is indicated by the lack of student response to the subject matter, students tend to be passive in learning. This study aims to improve student learning activeness through the application of the Problem Based Learning learning model. This type of research is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of several stages, namely planning, action implementation, observation and reflection. The subjects in this study were students in Class X Agribusiness of Food Crops and Horticulture of State Vocational High School 1 Hilimegai in the 2022/2023 academic year consisting of 31 students. The main techniques in data collection were observation, questionnaire and documentation. The results showed that in cycle I the average percentage of student learning activeness was 74%. In cycle II, the percentage of student learning activeness was 85%. Based on the percentage data for each cycle, there was an increase in student learning activeness. The conclusion of this study is that the Problem Based Learning (PBL) learning model can increase student learning activeness in ecosystem material in the X Agribusiness competency of food crops and horticulture at the State Vocational High School 1 hilimegai, 2022/2023 academic year.